2022
DOI: 10.3389/fnmol.2022.1017484
|View full text |Cite
|
Sign up to set email alerts
|

The validity of animal models to explore the pathogenic role of the complement system in multiple sclerosis: A review

Abstract: Animal models of multiple sclerosis (MS) have been extensively used to characterize the disease mechanisms in MS, as well as to identify potential pharmacologic targets for this condition. In recent years, the immune complement system has gained increased attention as an important effector in the pathogenesis of MS. Evidence from histological, serum, and CSF studies of patients supports an involvement of complement in both relapsing-remitting and progressive MS. In this review, we discuss the history and advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 192 publications
0
3
0
Order By: Relevance
“…It is also well established that activation of the immune complement system can occur as a result of brain injury and in neurodegenerative disorders ( Schartz and Tenner, 2020 ). Under pathological conditions such as those associated with traumatic brain injury, multiple sclerosis, and Alzheimer’s disease (AD), complement proteins, including C3, are linked to impaired cognitive functions ( Carpanini et al, 2019 ; Schartz and Tenner, 2020 ; Bourel et al, 2021 ; Saez-Calveras et al, 2022 ). In this study, we found SE-induced impairments in recognition memory in WT mice but not in C3 KO mice ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also well established that activation of the immune complement system can occur as a result of brain injury and in neurodegenerative disorders ( Schartz and Tenner, 2020 ). Under pathological conditions such as those associated with traumatic brain injury, multiple sclerosis, and Alzheimer’s disease (AD), complement proteins, including C3, are linked to impaired cognitive functions ( Carpanini et al, 2019 ; Schartz and Tenner, 2020 ; Bourel et al, 2021 ; Saez-Calveras et al, 2022 ). In this study, we found SE-induced impairments in recognition memory in WT mice but not in C3 KO mice ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, animal models involving complement deficiencies have been immensely helpful in dissecting complement-mediated pathological contributions to neurodegenerative and neuroinflammatory diseases and have served as pioneering platform for in vivo testing of complement inhibitors ( 240 ). However, most studies on complement in CNS pathologies have been performed using mice with global deficiencies in complement components of interest.…”
Section: Emerging Concepts and Considerationsmentioning
confidence: 99%
“…Immunohistochemical studies of postmortem MS brains have shown immunoreactivity for CCs, activation products, and complement regulators not only in plaque and periplaque areas but also in normalappearing white matter and cortical regions. 10,11 Several studies have also reported differences in the blood and CSF levels of CCs between patients with MS and healthy controls and between patients with different clinical forms of MS. [12][13][14] However, few of these studies were performed in patients with progressive MS and none of them evaluated long-term outcomes. Of interest, immunoreactivity for CCs has been observed in chronic active and inactive plaques of patients with progressive MS in the absence of other inflammation markers such as blood immune cells, indicating that progression of inflammation in MS does not depend on infiltrating cells and can be driven by innate immune mechanisms including complement activation.…”
Section: Introductionmentioning
confidence: 99%